The use of ICT during lockdown in higher education and the effects on university instructors. Issue 11 (November 2022) - Krassadaki, Evangelia; Tsafarakis, Stelios; Kapenis, Vassilis; Matsatsinis, Nikolaos
Abstract: During the pandemic, the Higher Education Institutions of Greece used Information and Communications Technologies (ICT) to an unprecedented degree to respond to the requirements of distance education and research work. The aim of this article is to present the main results of a nationwide quantitative survey that involved 1183 participating university instructors, to capture the impact of the use of ICT and its effects. Results show that, whereas the overall assessment of emergency remote teaching is positive, it seems that instructors have been challenged by the extreme use of technology. Women were mostly influenced, while age didn't have an impact. Significant differences among the participating university institutions were also discovered. Abstract : Higher Education; University teachers; COVID-19; ICT use.